Real-world utilization of aromatase inhibitors, tamoxifen, and ovarian function suppression in premenopausal patients with early hormone receptor-positive, HER2-negative breast cancer with increased recurrence risk - Müller, Volkmar; Hörner, Manuel; Thill, Marc; Banys-Paluchowski, Maggie; Schmatloch, Sabine; Fasching, Peter Andreas; Harbeck, Nadia; Langanke, Dagmar; Uhrig, Sabrina; Häberle, Lothar; Fischer, Dorothea; Hein, Alexander; et al. (The breast, 2025)
Background - The optimal adjuvant endocrine treatment in premenopausal patients with hormone receptor-positive, HER2-negative (HRpos/HER2neg) early breast cancer (eBC) remains debated, particularly the choice between aromatase inhibitors plus ovarian function suppression (AI + OFS) or tamoxifen (TAM) with or without additional OFS. This study assessed the use of adjuvant endocrine therapies for premenopausal patients with intermediate/high-risk HRpos/HER2neg eBC. - Methods - CLEAR-B (AGO-B-059; NCT05870813) was a retrospective study analyzing data, collected from January 2016 to June 2019 and from January 2022 to December 2023 during the certification process of breast centers in Germany. Premenopausal patients with HRpos/HER2neg intermediate/high-risk eBC were eligible. Patient and disease characteristics, in addition to recommended and received adjuvant treatments, were evaluated. - Results - The number of registered patients was 3137, of whom 2789 had complete information on endocrine treatments (1717 for 2016-2019 and 1072 for 2022-2023). In 2016-2019, 8.4 % of the patients were recommended to be treated with AI + OFS, whereas in 2022-2023, the proportion of patients with a treatment recommendation for AI + OFS rose to 42.1 %. In 2016-2019, TAM monotherapy was most frequently recommended (80.8 %). Conversely, TAM + OFS was not commonly recommended (9.3 % in 2016-2019 and 16.5 % in 2022-2023). While no clear association between tumor stage and chosen endocrine therapy was found in 2016-2019, most patients with ≥stage IIA were recommended to be treated with AI + OFS in 2022-2023. - Conclusion - This analysis shows that treatment recommendation for AI + OFS in premenopausal patients with HRpos/HER2neg eBC increased relevantly in the past years, reflecting latest guideline recommendations.
Online verfügbar: 22. März 2025, Artikelversion: 26. März 2025
Gesehen am 08.10.2025